Activism in regions of crime-related violence and corruption 2017-2019 - Stack, Trevor (UK Data Service, 2020)
By combining techniques such as structured interviews and direct observation in meetings and other events, the team sought to understand and compare activists’ diverse initiatives. This project studied activist responses to crime-related violence and corruption in the Mexican state of Michoacán. We understood activism as practices aimed at changing “the rules of the game” to achieve a more just society. In such difficult contexts as the Mexican state of Michoacán, activists are themselves often subject to violence, and hindered by corruption and other institutional failings. Despite this, we found that some of the many initiatives that we studied did help to mitigate the effects of violence and corruption, and to change some of the rules of the game that made them possible. Ethnographic fieldwork was conducted between 2017 and 2019 to elucidate regional differences as well as different kinds of activism. The project had the objective of evaluating the effectiveness of the different activist groups. Our comparative ethnographic approach enabled us to generate insights that were at once sensitive to local specifics and applicable to other parts of the world affected by crime, violence, and corruption. Although scholars and analysts suspect that civil society has the potential to mitigate the effects of criminal violence, few have conducted substantial research on the topic, and they have focused mainly on national (and international) civil organizations. We propose to focus on civil organizations based in the affected regions themselves, specifically within the west-central Mexican states of Michoacan and Jalisco, a region with high levels of criminal violence. It is increasingly recognized that treating organized crime as a matter of security is insufficient and can even exacerbate the problem, and that organized crime must be addressed through holistic strategies that include development consistent with human rights, providing opportunities for a dignified economic, social and political life outside the sphere of criminal organizations. In the state of Michoacan, for example, after "self-defence" vigilante groups ousted local police accused of serving organized crime in 2014, the federal government established a Commission for Security and Integral Development promising to deliver equitable and participative development to the region. Yet holistic strategies are notoriously difficult to execute when, as often in Mexico, state institutions in the affected regions are captured, wholly or partially, by the same criminal organizations and their associates. In these contexts, criminal organizations can for example use their hold over local (and state) government to frustrate the designs of national government, as well as of international agencies. Researchers and policy-makers suspect that civil society has an important role to play in these contexts. Civil society can monitor the actions of state institutions, insist on participating in development projects, resist development that hurts or fails to benefit vulnerable groups, and advocate strategies that do meet the needs of the broader population, thus helping to offset the hold of criminal organizations overhose institutions, as well as creating alternative livelihoods for the population. However, although there have been some studies of the role of national (and international) civil society in holding state institutions to account, the potential role of civil organizations within the regions themselves is little studied. This is our focus. The few studies conducted, and initial research by the applicants, suggest that civil society organizations are often themselves hemmed in by organized crime, and find it difficult to resist penetration by organized crime, much less to advance an agenda contrary to its interests. This helps to account, indeed, for the reluctance of many researchers to conduct sustained fieldwork in these contexts. Despite the forbidding panorama, the project will use comparative ethnography, following strict protocols designed to mitigate risk to researchers and research subjects, to identify and explain positive examples of organizations which have played an effective role in holding state institutions to a human rights agenda, and specifically one designed to offset the noxious effects of organized crime activities. Project outputs include an academic monograph co-authored by Guerra (CIDE), Maldonado (Colegio de Michoacán) and Stack (Aberdeen), and a volume edited by Stack to include papers from an international conference in London and others chapters co-authored by the applicants with the postdoctoral RAs. Unusually for an academic research project, we have chosen to put the policy outputs on an equal footing with the academic outputs. To this end, we have incorporated 2 policy analysts Domingo (ODI) and Jesperson (RUSI) as Co-Investigators. We have followed their instructions from the outset to ensure that the data collection and analysis will be adequate to the task of producing a series of well-grounded policy briefs, applicable to other regions of Mexico (and the world) affected by criminal violence.